Cervical Paraspinal Muscle Fatty Degeneration Is Not Associated with Muscle Cross-sectional Area: Qualitative Assessment Is Preferable for Cervical Sarcopenia. Issue 4 (April 2021) - Pinter, Zachariah W.; Wagner, Scott; Fredericks, Donald; Xiong, Ashley; Helgeson, Melvin; Currier, Bradford; Freedman, Brett A.; Kepler, Christopher; Elder, Benjamin D.; Bydon, Mohamad; Nassr, Ahmad; Sebastian, Arjun S.
Abstract: Background: Sarcopenia, defined as decreased skeletal mass, is an independent marker of frailty that is not accounted for by other risk-stratification methods. Recent studies have demonstrated a clear association between paraspinal sarcopenia and worse patient-reported outcomes and complications after spine surgery. Currently, sarcopenia is characterized according to either a quantitative assessment of the paraspinal cross-sectional area or a qualitative analysis of paraspinal fatty infiltration on MRI. No studies have investigated whether the cervical paraspinal cross-sectional area correlates with fatty infiltration of the cervical paraspinal muscles on advanced imaging. Question/purpose: Do patients undergoing anterior cervical discectomy and fusion (ACDF) with increasing paraspinal fatty degeneration on advanced imaging also demonstrate decreased cervical paraspinal cross-sectional area? Methods: Between 2011 and 2017, 98 patients were prospectively enrolled in a database of patients undergoing one- to three-level ACDF for degenerative conditions at a single institution. To be eligible for this prospective study, patients were required to undergo an MRI before surgery, be older than 18 years, and have no previous history of cervical spine surgery. Two independent reviewers, both surgeons not involved in the patients' care and who were blinded to the clinical outcomes, retrospectively assessed the paraspinal cross-sectional area and Goutallier classification of the right-sided paraspinal muscle complex. We then compared the patients' Goutallier grades with their paraspinal cross-sectional area measurements. We identified 98 patients for inclusion. Using the Fuchs modification of the Goutallier classification, we classified the fatty degeneration of 41 patients as normal (Goutallier Grades 0 to 1), that of 47 patients as moderate (Grade 2), and that of 10 patients as severe (Grades 3 to 4). We used ANOVA to compare all means between groups. Results: There was no difference in the mean paraspinal cross-sectional area of the obliquus capitus inferior (normal 295 ± 81 mm 2 ; moderate 317 ± 104 mm 2 ; severe 300 ± 79 mm 2 ; p = 0.51), multifidus (normal 146 ± 59 mm 2 ; moderate 170 ± 70 mm 2 ; severe 192 ± 107 mm 2 ; p = 0.11), or sternocleidomastoid (normal 483 ± 150 mm 2 ; moderate 468 ± 149 mm 2 ; severe 458 ± 183 mm 2 ; p = 0.85) among patients with mild, moderate, and severe fatty infiltration based on Goutallier grading. There was a slightly greater longus colli cross-sectional area in the moderate and severe fatty infiltration groups (74 ± 22 mm 2 and 66 ± 18 mm 2, respectively) than in the normal group (63 ± 15 mm 2 ; p = 0.03). Conclusion: Because our study demonstrates minimal association between paraspinal cross-sectional area and fatty infiltration of the cervical paraspinals, we recommend that physicians use the proven qualitative assessment of paraspinal fatty infiltration during preoperative evaluation of patients who are candidates for ACDF. Future studies investigating the relationship between cervical paraspinal cross-sectional area and patient-reported outcomes after ACDF are necessary to lend greater strength to this recommendation. Level of Evidence: Level III, diagnostic study.